High-sensitivity optical fiber hydrogen sensing with MoO3/PANI/Pd nanocomposite - Alkhabet, Mohammed M.; Girei, Saad H.; Farhan, Ammar H.; Hashim, Fatimah F.; Jaafar, Jaafar A.; Salih, Husam K.; Abbood, Manar F.; Yaacob, Mohd H. (Elsevier, 2025)
Hydrogen gas (H2) is increasingly used in clean energy and industrial sectors, but its high flammability necessitates sensitive and reliable detection systems. This study presents a tapered optical fiber hydrogen sensor coated with a MoO3/PANI/Pd nanocomposite, aiming to improve sensitivity, selectivity, and stability under room temperature. The nanocomposite was synthesized and characterized using FESEM, EDX, XRD, and AFM, confirming high surface roughness and uniform nanoparticle dispersion beneficial for gas adsorption. The sensor demonstrated high sensitivity (16.81/vol%), rapid response (90 s), and stable operation over one month with minimal drift, outperforming traditional sensors and MoO3 or MoO3/PANI-based configurations. Selectivity tests showed a significantly higher response to hydrogen compared to NH3 and CH4, confirming strong interference immunity. These results indicate the MoO3/PANI/Pd-coated tapered fiber sensor is a promising, scalable, and energy-efficient candidate for real-time hydrogen leak detection in industrial safety applications.